1999
DOI: 10.1016/s0924-9338(99)00169-8
|View full text |Cite
|
Sign up to set email alerts
|

Psychometric properties of the French version of the Composite Scale of Morningness in adults

Abstract: The objective of this study was to provide a reliable instrument to measure morningness for upcoming studies in French samples, using the Composite Scale of Morningness (CSM), which has been translated into French. Nursing students (n = 356) completed the questionnaire between February and March 1997. The total score obtained was independent of age and gender, and normally distributed. The reliability was high (Cronbach's alpha = 0.85), and factorial analysis confirmed the unidimensionality of the scale. Eveni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
24
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 39 publications
(32 citation statements)
references
References 8 publications
(35 reference statements)
8
24
0
Order By: Relevance
“…Although the concept of M/E and the instruments of M/E preference measurement have been standardized and widely used in Western populations, the items of these instruments were also proven to be applicable to Korean samples. Since an α above 0.7 is generally accepted as appropriate for rating scales dealing with psychological or biological constructs, the results of reliability tests suggest that the KtCS is comparable to the French or the Spanish versions in terms of internal consistency (26, 32).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the concept of M/E and the instruments of M/E preference measurement have been standardized and widely used in Western populations, the items of these instruments were also proven to be applicable to Korean samples. Since an α above 0.7 is generally accepted as appropriate for rating scales dealing with psychological or biological constructs, the results of reliability tests suggest that the KtCS is comparable to the French or the Spanish versions in terms of internal consistency (26, 32).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have demonstrated good test–retest reliability and adequate external validity for the CSM (20, 21, 24, 25). The CSM has been translated into several languages, including French, Italian, Spanish and Thai (24–28). It has also been translated into Korean and the Korean translation (i.e., KtCS) has been proven to have acceptable psychometric properties (23, 29).…”
Section: Methodsmentioning
confidence: 99%
“…There were moderate and highly significant correlations with all performance assessments in the expected direction. The correlations between CSM scores and physical peak performance were lower compared to Caci et al (1999;weekdays 70.51;weekends: 70.49), while correlations with cognitive/mental peak performance and CSM sores were higher (weekdays: 70.38, weekend: 70.38;Caci et al 1999 …”
Section: Physical and Cognitive Peak Performancementioning
confidence: 90%
“…Smith, et al (1989) created the Composite scale of morningness (CSM) by using the most validated questions from the MEQ and the Diurnal Type Scale (Smith et al, 1989). Subsequent studies have corroborated its reliability and validity (Bohle et al, 2001; Brown, 1993; Caci et al, 2005; Caci et al, 1999; Diaz-Morales and Sanchez-Lopez, 2005; Greenwood, 1994). We have found that it discriminates circadian variation among patients with bipolar disorder from control individuals in the US (Mansour et al, 2005; Wood et al, 2009); others have reported similar results from Korea (Ahn et al, 2008).…”
Section: Introductionmentioning
confidence: 85%
“…We have found that it discriminates circadian variation among patients with bipolar disorder from control individuals in the US (Mansour et al, 2005; Wood et al, 2009); others have reported similar results from Korea (Ahn et al, 2008). The CSM has been translated into several languages, including French (Caci et al, 1999), Korean (Ahn et al, 2008), Spanish (Diaz-Morales and Sanchez-Lopez, 2005), Italian (Natale et al, 2005), Thai (Pornpitakpan, 1998), Argentinean (Gil et al, 2008), German (Randler, 2008c), Romanian (Voinescu et al, 2010), Norwegian (Thun et al, 2012), Hindi (Bhatia et al, 2013), and Turkish (Onder et al, 2013). …”
Section: Introductionmentioning
confidence: 99%